Veganism, cuisine, and class: exploring taste as a facilitator in adopting a vegan lifestyle in Santiago, Chile - Giacoman, Claudia; Joustra, Camila (Frontiers in Sociology, 2024)
Introduction Veganism is a movement that avoids consuming animal products. This lifestyle is commonly represented as elitist despite the broad range of people who follow it. Using Bourdieu's taste theory, this study analyzes how personal culinary tastes of different social classes generate favorable (or unfavorable) dispositions to adopting veganism. Methods We analyzed 73 biographical interviews with 40 young vegans in three different waves. Results The findings reveal that all social classes exhibit favorable dispositions towards veganism. In upper-class individuals, dispositions to embrace healthy and exotic food facilitate the adoption of new flavors and reflexivity in eating practices. Conversely, lower-class individuals have traditional meatless culinary practices rooted in their restricted budget, facilitating the transition to a plant-based diet. Discussion These results demonstrate the relevance of social class in understanding the diversity of vegan practices, and they contribute to breaking stereotypes around this movement.